Continuous-wave electrically pumped multi-quantum-well laser based on group-IV semiconductors - Seidel, Lukas; Liu, Teren; Concepción, Omar; Marzban, Bahareh; Kiyek, Vivien; Spirito, Davide; Schwarz, Daniel; Benkhelifa, Aimen; Schulze, Jörg; Ikonic, Zoran; Hartmann, Jean Michel; Chelnokov, Alexei; et al. (Nature Communications, 2024)
Over the last 30 years, group-IV semiconductors have been intensely investigated in the quest for a fundamental direct bandgap semiconductor that could yield the last missing piece of the Si Photonics toolbox: a continuous-wave Si-based laser. Along this path, it has been demonstrated that the electronic band structure of the GeSn/SiGeSn heterostructures can be tuned into a direct bandgap quantum structure providing optical gain for lasing. In this paper, we present a versatile electrically pumped, continuous-wave laser emitting at a near-infrared wavelength of 2.32 µm with a low threshold current of 4 mA. It is based on a 6-periods SiGeSn/GeSn multiple quantum-well heterostructure. Operation of the micro-disk laser at liquid nitrogen temperature is possible by changing to pulsed operation and reducing the heat load. The demonstration of a continuous-wave, electrically pumped, all-group-IV laser is a major breakthrough towards a complete group-IV photonics technology platform.
CRIS-Team Scopus Importer:2025-02-04